P126 Female COPD patients have a greater prevalence of a low muscle mass and weaker quadriceps muscles than male patients. (12th November 2019) - Sathyapala, SA; Rochester, A; Kemp, PR; Brightling, C; Steiner, M; Polkey, MI
Abstract : Introduction: We recently reported that, in a cohort of 114 COPD patients, females had lower quadriceps strength and smaller type II muscle fibres than males, even after accounting for normal gender differences in health (Sharanya et al, 2019). Given the association of muscle dysfunction with impaired exercise capacity and mortality in COPD, we sought to confirm this finding in a larger, distinct cohort. Methods: Lung function, body composition (assessed using bioelectrical impedance) and quadriceps maximal voluntary contraction force (QMVC) measurements from 360 COPD patients (120F, 240M) from the COPD-MAP cohort were analysed. Patients were designated as having a low body mass index (BMI) using the WHO threshold of <21 kg/m 2, and a low fat-free mass index (FFMI) using the cut-offs validated for a secondary care COPD population (<15 kg/m 2 in females, 16 kg/m 2 in males, Schols et al 1993 and Mostert et al 2000). MVC was expressed as a percentage predicted using our prediction equations (Seymour et al 2010) that correct for gender and FFM. Comparisons were made using the Mann-Whitney U-test or t-test, and Fisher's exact test with proportions. Results: Females and males were matched for GOLD stage; however, females had slightly less severe airflow obstruction than males (see Table 1). Despite this, and that similar proportions of females and males had a low BMI, females had a greater prevalence of a low FFMI. Furthermore, females had lower quadriceps strength than males; this could not be explained solely by muscle atrophy as their lower muscle mass was corrected for in calculation of the predicted values. The proportion of female patients with a QMVC/BMI ratio of <120%, which predicts increased mortality (Swallow et al, 2007), was also higher than in males (see table 1). Conclusions: Female COPD patients have a higher prevalence of a low muscle mass than males. Furthermore, females have weaker quadriceps muscles than males, even after accounting for expected gender differences and for their lower muscle mass. Study of why female patients are weaker is required. The data also argues for female COPD patients to be monitored especially closely for these complications in the clinic.